Persepsi Pasien Pasca Bedah Mulut (Gusi) terhadap Sisa Makanan Lunak di Rumah Sakit Surya Husadha Denpasar - Komang Sugiantari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Soft food served in hospitals is a simple indicator that can be used to evaluate the success of hospital nutrition services. The aim of this study was to determine the perception of oral surgery patients regarding soft food waste at Surya Husadha Hospital Denpasar. This research uses a quantitative descriptive survey method. The total population was 30 people, the number of research samples was 20 people... data collection was carried out by measuring perceptions of taste and food waste using a questionnaire for the 20 samples studied. Data was obtained from filling out a questionnaire about perceptions of soft food and a form for the amount of food waste. The data was analyzed using SPSS version 21 statistical analysis. The results of this study showed that there were porridge food waste in 40-49% (45%) of the sample, 50-59% (40%) of the sample, 60-69% (15%) of the sample. Leftover animal side dishes (0%). Vegetable side dishes (10%). Leftover vegetables (10%) And for juice (0%). It can be concluded that the perception of soft food at Surya Husadha Hospital from this research shows that as many as 40-49% (45%) are not satisfied with the rest of the soft food (porridge).